2021
DOI: 10.3389/fimmu.2021.658660
|View full text |Cite
|
Sign up to set email alerts
|

Novel Host Protein TBC1D16, a GTPase Activating Protein of Rab5C, Inhibits Prototype Foamy Virus Replication

Abstract: Prototype foamy virus (PFV) is a member of the oldest family of retroviruses and maintains lifelong latent infection in the host. The lifelong latent infection of PFV may be maintained by the restriction factors of viral replication in the host. However, the mechanisms involved in PFV latent infection are poorly understood. Here, we found that TBC1D16, a TBC domain-containing protein, is significantly down-regulated after PFV infection. Tre2/Bub2/Cdc16 (TBC) domain-containing proteins function as Rab GTPase-ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 65 publications
0
9
0
Order By: Relevance
“…Recently, we have reported that an autophagy process could be induced by PFV infection, which participates in regulating PFV replication [ 10 ]. In addition, host factor Pirh2 (human p53-induced RING-H2 protein) and TBC1D16 have also been identified to repress PFV replication [ 11 , 12 ]. However, the underlying mechanism of PFV latent infection remains elusive.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, we have reported that an autophagy process could be induced by PFV infection, which participates in regulating PFV replication [ 10 ]. In addition, host factor Pirh2 (human p53-induced RING-H2 protein) and TBC1D16 have also been identified to repress PFV replication [ 11 , 12 ]. However, the underlying mechanism of PFV latent infection remains elusive.…”
Section: Introductionmentioning
confidence: 99%
“…To identify a candidate Rab5-GAP(s) that regulates endosome maturation, we first focused on the protein family members that share a TBC (Tre-2/Bub2/Cdc16)-domain, most of which are known to function as Rab-GAP domains ( Fukuda, 2011 ; Frasa et al, 2012 ). More than 40 TBC-domain-containing proteins (simply referred to as TBC proteins below) are present in mammals, and although some of them have been shown to exhibit GAP activity toward Rab5 in vitro ( Xiao et al, 1997 ; Pei et al, 2002 ; Chamberlain et al, 2004 ; Haas et al, 2005 ; Li et al, 2009 ; Lachmann et al, 2012 ; Rao et al, 2021 ; Yan et al, 2021 ), no attempt has ever been made to comprehensively screen for Rab5-GAPs in living cells or in vivo. If hyperactivation of Rab5 in Mon1 -KO cells is the primary cause of the greatly enlarged endosomes/lysosomes, forced inactivation of Rab5 by overexpressing TBC/Rab5-GAP proteins should decrease the size of the endosomes/lysosomes, the same as Rab5 knockdown did ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…In stroke studies, a large amount of evidence also proves that inhibiting TAK1-NF-κB can reduce I/R injury (Neubert et al, 2011). Although some TBC proteins participated in the regulation of antiviral and innate immunity (De Arras et al, 2012;Yan et al, 2021). To date, the relationship between TBC1D25 and inflammation has not yet been reported.…”
Section: Tbc1d25 Knockdown Promotes Cerebral I/r Injury Via Tak1-jnk/p38 Pathwaymentioning
confidence: 99%
“…TBC1D25 (TBC1Domain Family Member 25) is a ubiquitously expressed protein that contains a TBC (Tre-2/Bub2/Cdc16)/RAB-GTPase activating protein (GAP) domain. Studies have found that TBC domain proteins are associated with a variety of diseases, such as tumorigenesis, viral and bacterial infection susceptibility, circulatory and nervous system diseases (Finelli et al, 2019;Frasa et al, 2012;Harms et al, 2020;Yan et al, 2021;Yu et al, 2020). TBC1D15 could protect against cardiac injury by alleviating infarct area and reduced cardiomyocyte apoptosis in acute myocardial infarction (Yu et al, 2020).…”
Section: Introductionmentioning
confidence: 99%